Sliding Schottky diode triboelectric nanogenerators with current output of 10^9 A/m2 by molecular engineering of Si(211) surfaces - Lyu, Xin; Ferrie, Stuart; Pivrikas, A.; MacGregor, M.; Ciampi, Simone (ELSEVIER, 2022)
Triboelectric nanogenerators (TENGs) are an autonomous and sustainable power-generation technology, seeking to harvest small vibrations into electricity. Here, by achieving molecular control of oxide-free Si crystals and using conductive atomic force microscopy, we address key open questions and use this knowledge to demonstrate zero-applied-bias current densities as high as 109 A/m2. Key to achieve this output, is to use a proton-exchangeable organic monolayer that simultaneously introduces a sufficiently high density of surface states (assessed as changes to carrier recombination velocities) coupled to a strong surface dipole in the form of a surface alkoxide anion (Si–monolayer–O−). We also demonstrate that the DC output of a Schottky diode TENG does not track the energy released as friction. This removes the complexity of controlling an unavoidable stick–slip motion, bypassing the requirement of aligning sliding motion and substrate topographical features. We reveal that there is no apparent correlation between the current of a static (biased) junction and the tribocurrent of the same junction when under motion and unbiased.